Frequency and pattern reconfigurable rectangular patch antenna using single PIN diode - Palsokar, Anuradha A.; Lahudkar, S.L. (International journal of electronics and communications, 2020)
The paper presents the design of a frequency and pattern reconfigurable rectangular patch antenna using a single PIN diode switch. The use of single PIN diode reduces the complexity of the biasing network required for the diode. The proposed antenna can work in two different modes and resonates at 2.47 GHz, 3.8 GHz, and 5.36 GHz with the capability to change the radiation pattern. In this design biasing lines required for biasing of the diode are placed away from the radiating structure and the pattern search algorithm is used for the optimization of antenna feed for achieving impedance matching. These are the two improvisations made in the presented design as compared to the existing designs in literature.